Histological and histochemical study of effect of dietary fibre in motility of stomach in male mice - Khulood Ayad Majeed; Haider Abdal-Rasool Jaafar; Hussein Abbas Jarullah (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate the relationship between dietary fibres and muscularis externa layer. Method: The experimental study was conducted at the Anatomy Department of the College of Medicine, Al- Nahrain University, Iraq, from November 2020 to April 2021, and comprised adult healthy males. They were divided randomly into experimental group A and control group B. Group A was fed high-fibre diet, and group B was fed standard pellet diet. The tissue samples were harvested at day 30 post-surgery. The stomach samplings were placed in 10% neutral formalin for 24 hours to obtain paraffin sections for routine histological and immunohistochemical staining. The protein expression in stomach’s smooth muscle of each group was detected by immunohistochemical staining. Data was analysed using SPSS 24. Result: Of the 20 mice, 10(50%) were in each of the two groups. Group A exhibited significant weight-gain compared to group B (p less than or equal to 0.01). There was significant reduction in the thickness of the muscularis layer in group A compared to group B (p less than or equal to 0.01). Anoctamin 1 expression in group A was significantly lower than that in group B (p less than or equal to 0.01). Conclusion: The stress induced by an unstable fibre diet significantly affected the stomach by decreasing the muscularis layer thickness and Anoctamin 1 expression in interstitial cells of Cajal. Key Words: Anoctamin, Paraffin, Cajal, Formaldehyde